Evaluation of physical and psychosocial state of elderly using the NOSGER scale - Fidecki, Fidecki; Wysokiński, Mariusz; Wrońska, Irena; Kędziora-Kornatowska, Kędziora-Kornatowska; Kachaniuk, Hanna; Ślusarz, Robert; Burian, Jadwiga; Sienkiewicz, Zofia (Nursing in the 21st Century, 2013)
EVALUATION OF PHYSICAL AND PSYCHOSOCIAL STATE OF ELDERLY USING THE NOSGER SCALE Aim. The aim of the study was to asses physical and psycho-social state of the elderly staying in their home environments by means of the Nurses’ Observation Scale for Geriatric Patients (NOSGER). Material and methods. The study was carried out among 132 elderly people, aged 65 and over, living in Lubelskie, Podkarpackie and Podlaskie Voivodeships. The research material was collected by means of the NOSGER scale, which enables both professional and amateur caregivers of elderly people to perform a prompt and easy assessment of their patients’ physical, mental and social condition. The scale consists of 30 questions and covers six fields: i.e. memory, instrumental activities of daily living (IADL), activities of daily living (ADL), moods and emotions, social behaviours, destructive, disruptive and antisocial behaviours. Results. Having assessed patients by means of the NOSGER scale, 71.20% were included into the group described as the healthy subjects (they scored below 60 points), the group of the ill subjects comprised 28.80% of the total number (they scored over 60 points). Scores averaged at the level of 54.12, may be interpreted as an average level of psychosocial and physical fitness. Conclusions. The NOSGER scale is a useful tool for assessing geriatric patients’ condition and allows specifying self-care deficiencies. Persons participating in the study proved to suffer from greatest functional ability deficiencies within instrumental everyday life activities. Those with higher education as well as the married people tended to enjoy greater fitness.